Stabilisation of excavated slopes in strain softening materials with piles - Summersgill,F; Kontoe,S; Potts,DM (Géotechnique, 2018)
The use of a row of discrete vertical piles is an established method, successfully used to remediate failure of existing slopes and to stabilise potentially unstable slopes created by widening transport corridors. This paper challenges the assumptions made in current design procedures for these piles, which treat the pile only as an additional force or moment and simplify soil–pile interaction. Two-dimensional plane-strain finite-element analyses were performed to simulate the excavation of a slope in a stiff clay and the interaction of vertical piles within the slope. A non-local strain-softening model was employed for the stiff clay to reduce the mesh dependency of the solution. An extensive parametric study was performed to systematically examine the impact of pile position, dimensions (length and diameter) and time of pile construction on the stability of a cutting in London Clay, which was chosen as a representative strain-softening material. A variety of different failure mechanisms were identified, depending on pile location, dimensions and time of construction. The variability of the pile and slope interaction that was modelled suggests that an oversimplification during design could miss the critical failure mechanism or provide a conservative stabilisation solution. Given the prevalence of stiff clay slopes in the UK, increased capacity requirements of transport infrastructure and the age of slopes in this material, an informed and more realistic design of stabilisation piles will become increasingly necessary.